Pengaruh Sponsor Eksekutif , Teknologi Informasi dan Manajemen data terhadap Keberhasilan Executive Information System - Gerson Manurung; Hapzi Ali (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
The effect of Sponsor Eksekutif , Teknologi Informasi and Manajemen data on Keberhasilan Executive Information System is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries , Google Scholar , Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) Sponsor Eksekutif has an effect on Keberhasilan Executive Information System; 2) Teknologi Informasi has an effect on Keberhasilan Executive Information System; and 3) Manajemen data has an effect on Keberhasilan Executive Information System.